Domestic versus External Public Debt in Jordan: an Empirical Investigation - Alshyab, Nooh (Jordan Journal of Economic Sciences, 2015)
The purpose of this study is to investigate the growth implications of public debt in Jordan, disentangling the effects of external and domestic components. The empirical analysis is based on a neoclassical growth model, relying on a Cobb Douglas function with capital, labor, and public debt as independent factors of production. The model has been tested with three different specifications of the variable public debt, namely, total, domestic, and external debt. A Johansen cointegration approach was adopted to test the long run relationship between these variables and economic growth on data series for 1980-2013. On this data set, also Vector Error Correction Model and Granger causality have been tested. The study provides evidence for a negative effect of public debt on economic growth. Further, the negative contribution of domestic debt to economic growth seems to be of similar magnitude than the contribution of external debt.